The HTLV-1 oncoprotein Tax is modified by the ubiquitin related modifier 1 (Urm1) - Hleihel, Rita (Retrovirology, 2018)
BACKGROUND: Adult T-cell leukemia/lymphoma (ATL) is an aggressive malignancy secondary to chronic human T-cell lymphotropic virus 1 infection, triggered by the virally encoded oncoprotein Tax. The transforming activity and subcellular localization of Tax is strongly influenced by posttranslational modifications, among which ubiquitylation and SUMOylation have been identified as key regulators of the nuclear/cytoplasmic shuttling of Tax, as well as its ability to activate NF-κB signaling. RESULTS: Adding to the complex posttranslational modification landscape of Tax, we here demonstrate that Tax also interacts with the ubiquitin-related modifier 1 (Urm1). Conjugation of Urm1 to Tax results in a redistribution of Tax to the cytoplasm and major increase in the transcription of the NF-ĸB targets Rantes and interleukin-6. Utilizing a tax-transgenic Drosophila model, we show that the Urm1-dependent subcellular targeting of Tax is evolutionary conserved, and that the presence of Urm1 is strongly correlated with the transcriptional output of Diptericin, an antimicrobial peptide and established downstream target of NF-κB in flies. CONCLUSIONS: These data put forward Urm1 as a novel Tax modifier that modulates its oncogenic activity and hence represents a potential novel target for developing new strategies for treating ATL.